2021
DOI: 10.22219/kembara.v7i1.15805
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of doing task-based language teaching in Indonesia: Teachers’ perception

Abstract: Task-based language teaching (TBLT) has received significant attention from both researchers and practitioners of second language learning. This approach has been reported to be effective in various contexts. Studies on the teachers’ perception on TBLT have also been conducted. The results inform the perceived benefits and challenges of using TBLT in teaching context. However, very few studies have investigated the teachers’ perception in Indonesian context. To investigate the perception, a qualitative researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Furthermore, there was a similarity between the teacher's problem regarding the difficulty in preparing the materials in this study, with the one found in the study by previous researcher. The study found that teacher also felt that the implementation of Task-Based Learning was time-consuming in terms of the preparation (Hima et al, 2021). It was just as how this study found that the teacher at SMAS Candimas Pancasari faced difficulty in preparing the right media and tools that must be adapted to the learning activities.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, there was a similarity between the teacher's problem regarding the difficulty in preparing the materials in this study, with the one found in the study by previous researcher. The study found that teacher also felt that the implementation of Task-Based Learning was time-consuming in terms of the preparation (Hima et al, 2021). It was just as how this study found that the teacher at SMAS Candimas Pancasari faced difficulty in preparing the right media and tools that must be adapted to the learning activities.…”
Section: Discussionmentioning
confidence: 78%
“…All of these changes certainly affect the implementation of the learning methods and models used by the teachers regarding the Curriculum 2013, including the implementation of Task-Based Learning. Implementing a Task-based Learning model in a face-to-face teaching and learning process is certainly different from implementing it in an online situation (Baralt, 2017;Hima et al, 2021). More effort is needed in the online learning process since teachers need to manage both the interaction and the students' engagement as monitoring is harder to be done (Kandari, 2020;Stickler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The application of 4C competencies, creativity, communication skills, and collaborative has also implemented strengthening character education in the learning process, implementation plans. The learning process (RPP) has been structured according to existing standards, the learning process is in accordance with what is in the supervision instrument, and teachers are still trying to improve their competence in teaching such as applying various learning models (Hima et al, 2021;Putri & Sulistyaningrum, 2021;Sulaiman & Ismail, 2020). Teachers' pedagogical competencies in 21st century teacher skills include skills in encouraging, supporting and modeling student inventions and creative and innovative thinking (Ana et al, 2020;Chong et al, 2019;Ferreira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Planning is carried out by designing the learning that will be carried out in the form of rpp that will be used. The preparation of the RPP must pay attention to and integrate 1) Strengthening Character Education (PPK) in learning, 2) literacy, 3) 21st century skills and Hots (Hima et al, 2021;Stehle & Peters-Burton, 2019). Current rpps must integrate technology as an effort to introduce and familiarize teachers and students with technology.…”
Section: Discussionmentioning
confidence: 99%